Early Access to Support for Families of Foreign Origin in Japan: An Exploratory Study of Social Work Outreach utilizing Web Advertising - Ohsaka, Yuki (Indonesian Social Work Consortium (ISWC), 2025)
This study reconceptualizes outreach as a preventive social work practice aimed at facilitating early access to support for individuals and families who remain invisible to formal support systems, with a particular focus on families of foreign origin (FFO) in Japan who face structural and social barriers to accessing support information. To empirically examine this form of preventive outreach, the study analyzes the outcomes of a multilingual web advertisement campaign implemented by a Japanese non-profit organization Florence. The analysis draws on outreach activities conducted through Global Oyako Chat initiative, which disseminated support information in English, Tagalog, and Vietnamese language. Data, such as number of ads displayed (n = 2,643,927), click-throughs (n = 18,467), and “Add Friend” button clicks (n = 343) were analyzed and further disaggregated by language, users’ gender, device type, and residential area to identify patterns of engagement and access behavior. The findings indicate that, in contrast to conventional outreach that primarily targets “visible clients” whose challenges are already apparent, web-based outreach enables connection with “invisible clients” whose needs may be unrecognized or have not yet fully emerged. This approach can be characterized as a form of preventive outreach, enhancing early access to support before problems escalate. The findings suggest that, when thoughtfully designed and implemented, digital outreach strategies can help bridge structural gaps and improve access to support information for underserved FFO communities in Japan.